On the road - Kerouac, Jack, 1922-1969. (New York : Penguin, 1976)
Presents a thinly fictionalized autobiography of Jack Kerouac's cross-country adventure across North America on a quest for self-knowledge as experienced by his alter-ego, Sal Paradise and Sal's friend Dean Moriarty.
Wilson's Fiction.
Young Adult
Keywords: Beat generation -- Fiction; Beat generation -- Fiction